(untitled) (Acta Scientiarum. Animal Sciences, 2018)
The present study aimed to evaluate the activation characteristics of the lebranche mullet spermatozoa in natura and diluted with CF-HBSS for 96h at 4±2°C. The semen was collected from eight wild fish in Florianópolis – SC (Brazil) (27°S) in May, during reproductive migration. Three pools of semen were divided into two treatments: in natura and diluted with CF-HBSS 1:3. The semen was activated with seawater (salinity of 34, pH 8.7 and 4±2°C) to determine: motility time, motility rate and sperm cell membrane integrity. Dilution with CF-HBSS 1:3 increased motility time of diluted semen (15-20% for 6, 12 and 18h). Motility rate was equal to fresh semen for up to 24h of refrigeration and it was 30% higher than in natura semen at 12, 18 and 24h. Cell membrane integrity was maintained in fresh semen up to 6h, and it was 15-20% higher than in natura semen from 6 to 48h (p < 0.05). The use of CF-HBSS as diluent in the ratio 1:3 is recommended for semen refrigeration of lebranche mullet.